Economic Empowerment of Pesantren through BUMP Program (Pesantren Owned Enterprises) - Bekti Widyaningsih; Nur Sa'adah; Mustamim Mustamim (INCOME: Innovation of Economics and Management, 2021)
This paper discusses the economic empowerment of pesantren through bump program at Pondok Pesantren Fathul Ulum Jombang. This paper is motivated by the role of boarding schools that are expected to be dynamicators and catalysts for the empowerment of human resources, drivers of development in all fields, especially in the economic field. BUMP is a business entity that is structurally under the auspices of Pesantren Fathul Ulum and has a position equivalent to other institutions of Pesantren Fathul Ulum. BUMP is managed by students who have been educated in accordance with their respective fields and assisted by the community as fast as. The authors of this study aimed to find out how the application and relevance of bump program is applied as a boarding school empowerment located in Pondok Pesantren Fathul Ulum Jombang. The method of writing used in this writing is to use descriptive qualitative by using field research. The types of data used in this study are primary data and secondary data taken from related sources. The discussion shows that the economic empowerment of pesantren through bump program implemented in Pondok Pesantren Fathul Ulum Jombang has been running well but it will be more relevant if the organizational structure can be improved so that it will run more effectively.